2007
DOI: 10.1080/10284150701406752
|View full text |Cite
|
Sign up to set email alerts
|

GM1 and NGF modulate Ca2+homeostasis and GAP43 mRNA expression in cultured dorsal root ganglion neurons with excitotoxicity induced by glutamate

Abstract: Monosialoganglioside (GM1) has been considered to have a neurotrophic factor-like activity. Nerve growth factor (NGF), a member of the neurotrophin family, is essential for neuronal survival, differentiation and maturation. The aim of the present study was to investigate whether co-administration of GM1 and NGF reverses glutamate (Glu) neurotoxicity in primary cultured rat embryonic dorsal root ganglion (DRG) neurons. DRG neurons were exposed to Glu (2 mmol/1), Glu (2 mmol/1) plus GM1 (10 microg/ml), Glu (2 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…GAP-43 expression increased in the injured nerve and in the corresponding DRG after peripheral nerve injury (Kato et al 2010). The expression of GAP-43 in cultured DRG neurons was affected by different drugs or factors, such as a nucleoside reverse transcriptase inhibitor 2 0 ,3 0 -dideoxycytidine (zalcitabine), an immunophilin ligand FK506 (Keswani et al 2004), brain-derived neurotrophic factor (BDNF) (Gupta et al 2009), monosialoganglioside and nerve growth factor (Huang et al 2007). Interestingly, GAP-43 is an important mediator of the neurotrophic effects of S18986 (a positive AMPA receptor modulator) and BDNF on neuronal survival and plasticity (Gupta et al 2009).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…GAP-43 expression increased in the injured nerve and in the corresponding DRG after peripheral nerve injury (Kato et al 2010). The expression of GAP-43 in cultured DRG neurons was affected by different drugs or factors, such as a nucleoside reverse transcriptase inhibitor 2 0 ,3 0 -dideoxycytidine (zalcitabine), an immunophilin ligand FK506 (Keswani et al 2004), brain-derived neurotrophic factor (BDNF) (Gupta et al 2009), monosialoganglioside and nerve growth factor (Huang et al 2007). Interestingly, GAP-43 is an important mediator of the neurotrophic effects of S18986 (a positive AMPA receptor modulator) and BDNF on neuronal survival and plasticity (Gupta et al 2009).…”
Section: Introductionmentioning
confidence: 97%
“…influx (Sanelli et al 2007). There is now convincing evidence that excessive accumulation of the excitatory amino acid Glu in the extracellular space is toxic to central mammalian neurons (Michaels and Rothman 1990) and peripheral neurons (Huang et al 2007). The presence of IGF-1 is required to depress the rise in intracellular Ca 2?…”
Section: Introductionmentioning
confidence: 99%
“…GM1 ganglioside is protective against various neurological insults, including excitotoxicity, calcium imbalance, membrane structure and integrity damage, etc. (Vorwerk et al 1999;Wu et al 2004;Huang et al 2007). Gangliosides may activate different Trk receptors by differentially affecting the release of neurotrophins (Rabin et al 2002).…”
Section: Discussionmentioning
confidence: 96%
“…The neuroprotective effects of GM1 ganglioside include several aspects such as reducing neuronal damage, preserving membrane structure and integrity, and restoring Ca(2+) homeostasis (Huang et al 2007;Vorwerk et al 1999;Wu et al 2004). It has been shown that GM1 facilitates the phenotypic recovery of motoneurons in the retrodorsal lateral nucleus of the spinal cord during aging and after axotomy (Goettl et al 2003).…”
Section: Introductionmentioning
confidence: 97%
“…There has been convincing evidence that excessive extracellular accumulation of Glu is toxic to the central [11] and the peripheral neurons [12] . IGF-1 is a neurotrophic [13][14][15][16] and potent anti-apoptotic factor [17,18] .…”
Section: Introductionmentioning
confidence: 99%